Implementation of Performance Appraisal System Based on Objectives and Key Results (OKR) at PT. Bintang Terang Sejati - Jacelyn Jacelyn; Alden Nelson (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
Evaluating performance is essential for determine the level of success and accomplishments possible for each employee. Implementing Objectives and Key Results (OKR) is essential for enhancing efficiency and achieving desired outcomes. This study aims to evaluate the impact of an OKR-based performance appraisal system with a rating scale method, using data from interviews, observations, and documentation. The findings support initiatives to boost productivity, motivation, and goal attainment, indicating positive transformations within the company, including a heightened focus on meeting deadlines and clearer, measurable key results for teams, resulting in greater punctuality and a more precise understanding of achievement levels.